2016
DOI: 10.1002/2015je004879
|View full text |Cite
|
Sign up to set email alerts
|

Insights into complex layered ejecta emplacement and subsurface stratigraphy in Chryse Planitia, Mars, through an analysis of THEMIS brightness temperature data

Abstract: Layered ejecta craters on Mars have been interpreted to indicate the presence of volatiles in the substrate, making them important targets for the investigation of sites of astrobiological significance. If the ejecta are associated with the presence of water in the substratum, specific surface grain size trends are expected. In this study we explore the distribution of grain sizes in the layered ejecta of impact craters located in Chryse Planitia, using Thermal Emission Imaging System (THEMIS) thermal infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 149 publications
2
11
1
Order By: Relevance
“…Insets 3 and 4 show different possibilities for the ascent off liquefied sediment and were derived from Mazzini and Etiope (2017) and Skinner and Mazzini (2009), respectively. They show that sediment from several strata in the stratigraphy may have contributed to the extrusions, consistent with the complex stratigraphy in Chryse Planitia (Jones et al, 2016). This is also the case for the spatial distribution of the observed edifices at local scale.…”
Section: Journal Of Geophysical Research: Planetssupporting
confidence: 72%
See 2 more Smart Citations
“…Insets 3 and 4 show different possibilities for the ascent off liquefied sediment and were derived from Mazzini and Etiope (2017) and Skinner and Mazzini (2009), respectively. They show that sediment from several strata in the stratigraphy may have contributed to the extrusions, consistent with the complex stratigraphy in Chryse Planitia (Jones et al, 2016). This is also the case for the spatial distribution of the observed edifices at local scale.…”
Section: Journal Of Geophysical Research: Planetssupporting
confidence: 72%
“…Such a sedimentary architecture may have favored the release of sedimentary volcanic material with different water content and effusion rates from different depths, perhaps even at the same time (see inset 4 in Figure 7b). A complex stratigraphy of Chryse Planitia has indeed been independently suggested on the basin of layered impact crater ejecta characteristics (Jones et al, 2016). A stack of sedimentary layers containing substantial portions of mud (Jöns, 1985) and some volcanic material (Scott & Tanaka, 1986), possibly hosting aquifers (Rodríguez et al, 2007), and ice layers or lenses (Carr & Head, 2019) would be a plausible source for liquefaction, subsurface sediment mobilization, and sedimentary volcanism.…”
Section: Geologic Implicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…In this model we treat the FAE as ground-hugging continuous flows similar to landslides, debris flows, granular flows, or snow avalanches, which is consistent with how Martian fluidized ejecta have been interpreted to have been deposited and has been observed in laboratory ejecta experiments (e.g., Jones et al, 2016; Mouginis-Mark & Baloga, 2006; Runyon & Barnouin, 2018). In the model proposed here (equation (3)) we establish upper bound values for the coefficient of sliding friction encountered by FAE on Ceres by ignoring flow within the cohesive mass of ejecta.…”
Section: The Hybrid Kinematic-dynamic Sliding Ejecta Emplacement Modelsupporting
confidence: 56%
“…In contrast, Jones et al. () reported that several DLE craters exhibited larger particles at the ejecta margins, but our detailed review of these craters suggests that they are unlikely to be DLE craters and require updated classification. We suggest that the presence of surface ice at the time of DLE crater formation is ultimately responsible for the observations discussed above.…”
Section: Ejecta Comparison With Landslidescontrasting
confidence: 61%